2003
DOI: 10.1097/00006416-200309000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of T’ai Chi Exercise on Fibromyalgia Symptoms and Health-Related Quality of Life

Abstract: Knowledge of interventions to enhance health for the patient with musculoskeletal problems is a National Association of Orthopaedic Nurses priority. Tai Chi is potentially beneficial to patients with FM. Further research is needed to support evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 39 publications
2
42
1
3
Order By: Relevance
“…13,34 Our findings are also consistent with observations from other clinical trials and meta-analyses that support the benefits of physical exercise and mind-body practice for symptom management in fibromyalgia. [35][36][37][38][39][40][41] The biologic mechanisms by which tai chi might affect the clinical course of fibromyalgia remain unknown.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…13,34 Our findings are also consistent with observations from other clinical trials and meta-analyses that support the benefits of physical exercise and mind-body practice for symptom management in fibromyalgia. [35][36][37][38][39][40][41] The biologic mechanisms by which tai chi might affect the clinical course of fibromyalgia remain unknown.…”
Section: Discussionsupporting
confidence: 89%
“…11,12 A small, nonrandomized study showed that tai chi reduced symptoms and improved quality of life in patients with fibromyalgia, 13 and it has also been shown to have potential therapeutic benefits in patients with other chronic rheumatic conditions, such as rheumatoid arthritis and osteoarthritis. 14,15 We conducted a single-blind, randomized, controlled trial to compare the physical and psychological benefits of tai chi with those of a control intervention that consisted of wellness education and stretching.…”
mentioning
confidence: 99%
“…Therefore, it is potentially beneficial to fibromyalgia patients but further research is needed to support the evidence-based practice (Taggart et al, 2003).…”
mentioning
confidence: 99%
“…Seven observational studies with relatively large sample sizes reinforced the beneficial association between Tai Chi practice and psychological health. Notably, the review found that Tai Chi tended to reduce depression compared to various controls among individuals with osteoarthritis (Fransen et al, 2007;Wang et al, 2009), rheumatoid arthritis (Wang, 2008b) fibromyalgia (Taggart et al, 2003;Wang et al, 2010b), depression disorders (Chou et al, 2004), sedentary obese women (Dechamps et al, 2009), and elderly participants with cardiovascular disease risk factors (Taylor-Piliae et al, 2006). This positive result was associated with improvement in symptoms and physical function in patients with rheumatoid arthritis and other chronic conditions.…”
Section: Scientific Evaluation Of Tai Chi For Rheumatoid Arthritismentioning
confidence: 99%